Prediction of Post-operative Visual Deterioration Using Visual-Evoked Potential Latency in Extended Endoscopic Endonasal Resection of Craniopharyngiomas - Tao, Xiaorong; Yang, Xiaocui; Fan, Xing; You, Hao; Jin, Yanwen; Liu, Jiajia; Guo, Dongze; Li, Chuzhong; Qiao, Hui (Frontiers in Neurology, 2021)
Background: The current study aimed to investigate the predictive value of visual-evoked potential (VEP) latency for post-operative visual deterioration in patients undergoing craniopharyngioma resection via extended endoscopic endonasal approach (EEEA). Methods: Data from 90 patients who underwent craniopharyngioma resection via EEEA with intraoperative VEP monitoring were retrospectively reviewed. P100 latency was compared between patients with and without post-operative visual deterioration, and the threshold value of P100 latency for predicting post-operative visual deterioration was calculated by the receiver operating characteristic curve analysis. In addition, other potential prognostic factors regarding post-operative visual outcomes were also analyzed by multivariate analysis. Results: Patients with post-operative visual deterioration showed a significantly longer VEP latency than those without (p < 0.001). An extension over 8.61% in VEP latency was identified as a predictor of post-operative visual deterioration (p < 0.001). By contrast, longer preoperative visual impairment duration and larger tumor volume were not significant predictors for post-operative visual deterioration. Conclusions: The current study revealed that intraoperative VEP monitoring in EEEA is effective for predicting post-operative visual deterioration, and an extension over 8.61% in VEP latency can be used as a critical cut-off value to predict post-operative visual deterioration.